Disparities and Divided Growth: Ethnic Entrepreneurship in the Greater Los Angeles Area, 1980–2015. (15th March 2018) - Wang, Qingfang
Abstract: This study employs a multilevel research design to examine business ownership across ethnic groups in the greater Los Angeles area. It finds significant divide between white and non‐white businesses along the labor market hierarchy. The entrepreneurial environment, ethnic residential communities, ethnic business spatial clustering, ethnic concentration in particular niche sectors, and ethnic diversity in local areas are all related to business ownership and disparities across ethnic groups. The results suggest that ethnically diverse neighborhoods and co‐ethnic business communities could provide a conducive institutional environment and resources for minority businesses to start. However, in contrast to white owned businesses, ethnic minority businesses' concentration in the low‐end and easy‐entry sectors may reinforce their disadvantages and hinder upward economic mobility. This study provides policy implications for community regional development through entrepreneurship especially when race and ethnicity are concerned.